Seeing with our own eyes: youth reveal strengths in Mathare using photovoice - Parker, Sarah Noyes, author; Dakin, Emily, advisor; Amell, Jim, advisor; Banning, Jim, committee member (Colorado State University. Libraries, 2010)
In this study, adolescent residents of the Mathare slum of Nairobi, Kenya documented their strengths and the strengths of their community using the Photovoice methodology, a participatory qualitative research approach. This study also sought to explore the utility of the Photovoice method for empowering youth in the Mathare slum and as a tool for social action. Research was conducted in collaboration with the Mwelu Foundation, a youth based photography program in Mathare slum. Adolescent and community strengths were a focus of this project given that the majority of prior research related to the Mathare slum has been oriented towards documenting its deplorable conditions with a lack of focus on its capabilities and resources. Template analysis was used to code the data, with resilience, resourcefulness, identity, purpose, and community resources emerging as themes related to adolescent and community strengths. Empowerment of the Mathare youth and social action related to the Mathare slum are deemed viable outcomes of the Photovoice method. Implications of the relevance of the photovoice method for social work practice are discussed.
Covers not scanned.
Keywords: Youth -- Kenya -- Nairobi; Documentary photography -- Kenya -- Nairobi